Sukces innowacji produktowej na współczesnym rynku i jego determinanty na wybranych przykładach - Miłota, Krzysztof (The Success of Product Innovation on the Modern Market and its Determinants - by Selected Examples, 2007)
Manufacturers introduce thousands of innovations into the market, but only few of them successfully. There are a few deciding factors that make some of them bring profits. Among those factors we the crucial ones: the ability to reach both potential consumer's attention and the nearest shop as well as the ability to manage perceived risk. Experiences of companies like Maspex that introduce several dozen of innovations per year enable them to act effectively in both mentioned areas, and should be analyzed by scientists. This will lead us to better understanding of the market mechanism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 122-132